THE EFFECT OF MARKETING MIX, SELF-SERVICE TECHNOLOGY, AND DIGITAL BANKING ON CUSTOMER SATISFACTION AT INDONESIAN SHARIA BANK PEKALONGAN PEMUDA - Hendri Hermawan Adinugraha; Mochamad Yusuf; Muhammad Taufiq Abadi (Journal of Management and Islamic Finance, 2022)
Indonesian Sharia Bank has a growing number of customers every year. The increase in customers is not matched by the quality of service in the form of customer satisfaction. Customer satisfaction is still an obstacle to maximizing Islamic banks' profits. This study aims to examine the influence of marketing mix, self-service technology, and digital banking on customer satisfaction at Indonesian Sharia Bank of Pekalongan Pemuda Branch. The sample was 100 respondents from a population of 48,200. The sample used simple random sampling. The method used a questionnaire. Instrument testing, classical assumption analysis, multiple linear regression analysis, and hypothesis testing were used to analyze the data. The results of the analysis conducted on customer satisfaction at Indonesian Sharia Bank of Pekalongan Pemuda Branch, include the self-service technology effect where tcount<ttable is 0.00<0.05, so H0 and Ha are accepted. Moreover, digital banking variables, have an effect where tcount<ttable is 0.00<0.05, then H0 and Ha are accepted on customer satisfaction. However, the marketing mix has no effect where tcount>ttable is 0.128>0.05, so H0 and Ha are rejected on customer satisfaction. The results show the 3 variables dependent with a significant value of 0.000<0.50 on Customer Satisfaction.